2017
DOI: 10.1128/jvi.00406-17
|View full text |Cite
|
Sign up to set email alerts
|

Structural Mimicry of the Dengue Virus Envelope Glycoprotein Revealed by the Crystallographic Study of an Idiotype–Anti-idiotype Fab Complex

Abstract: A detailed understanding of the fine specificity of serotype-specific human antibodies is vital for the development and evaluation of new vaccines for pathogenic flaviviruses such as dengue virus (DENV) and Zika virus. In this study, we thoroughly characterize the structural footprint of an anti-idiotype antibody (E1) specific for a potent, fully human DENV serotype 1-specific antibody, termed HM14c10, derived from a recovered patient. The crystal structure at a resolution of 2.5 Å of a complex between the Fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…The same could be explored to develop therapeutics ( 164 ). E1 was able to detect HM14c10- and HM14c10-like antibodies in the sera of patients who recovered from DENV infection ( 165 ), which suggested that it is a common idiotype and could be further tailored to obtain the desired results, including broader neutralization capability and diminished ADE.…”
Section: Fab Antibodiesmentioning
confidence: 99%
“…The same could be explored to develop therapeutics ( 164 ). E1 was able to detect HM14c10- and HM14c10-like antibodies in the sera of patients who recovered from DENV infection ( 165 ), which suggested that it is a common idiotype and could be further tailored to obtain the desired results, including broader neutralization capability and diminished ADE.…”
Section: Fab Antibodiesmentioning
confidence: 99%
“…Using hen egg lysozyme (HEL) as a model antigen, structural immunologists discovered that both the anti-HEL antibody (D1.3) and its anti-idiotypic antibody (E5.2) could bind to the D1.3 combining site ( 54 ). A previous study also documented that an anti-idiotype Fab E1 can partially mimic the E protein of Dengue virus ( 55 ). Few reports have confirmed that anti-idiotype antibodies completely mimic the antigen in structure and function ( 56 ).…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, E5.2 and lysozyme, which both bind D1.3 with similar affinities, share 13 contact residues, indicating that E5.2 is a good structural mimic for lysozyme. More recently, Wong and co-workers identified the antiidiotype Fab E1 to be a partial structural mimic for Dengue virus E protein 53 . These studies support the idea of structural mimicry, which originated purely from the observed binding properties of antibodies 35,36 .…”
Section: Discussionmentioning
confidence: 99%